Fluoxetine prevents the cognitive and cellular effects of chemotherapy in the adult hippocampus - Lyons, Laura (2011)
Rationale: CMF (cyclophosphamide: CP; methotrexate: MTX; 5-fluorouracil: 5-FU) is a chemotherapy combination associated with the cognitive impairments which many cancer patients experience after treatment. A reduction in hippocampal neurogenesis is a known means by which cytotoxic drugs alter cognition and is the mechanism investigated in the present study. There is currently no way of treating or preventing the cognitive deficits produced by chemotherapy and a simple pharmacological approach to achieving this could potentially have significant benefits for patients.